Commercial yeast inoculation effect on kinetic and microbiology of fermentative process and its relation to the sensorial quality of wine. A preliminary studi in patagonian Pinot Noir winemaking. - Curilén, Yolanda Leticia; Barda, Nora Beatriz; Barbagelata, Raúl Jorge; Bravo Ferrada, Bárbara Mercedes; Gallina, Mario Fabian; Semorile, Liliana Carmen; Caballero, Adriana Catalina (Asociación Argentina de Tecnólogos Alimentarios (AATA), 2025)
Vitis Vinifera L. cv. Pinot noir grapes from a Patagonian vineyard were fermented at pilot scale (100L) in spontaneous form (natural fermentation, NF) or by inoculation with a Saccharomyces cerevisiae commercial starter (guided fermentation, GF). Their kinetic behaviors and microbial (yeasts and lactic acid bacteria) populations as well as physical-chemical composition and sensorial response of their wines were characterized. Significant changes in the initial yeast diversity biota produced by the commercial yeast inoculation affected the winemaking process kinetic at the beginning phase, where extractive processes occur. Additionally, a negative effect on malolactic fermentation induction and development was also observed in GF. Changes in lactic acid bacteria biota quality or in yeasts-LABinteractions could be the causes of this fact. As a consequence, NF and GF wines showed different sensory qualities which were found to be better in the former. In particular, NF wines had a higher color intensity, mouth persistence and flavor (aroma and taste) complexity. These differential responses to the sensorial analysis were consistent with the data obtained from the physicochemical analysis of these wines.